The missing Spanish creoles : recovering the birth of plantation contact languages - McWhorter, John H. (University of California Press, 2000)
John McWhorter challenges an enduring paradigm among linguists in this provocative exploration of the origins of plantation creoles. Using a wealth of data--linguistic, sociolinguistic, historical--he proposes that the "limited access model" of creole genesis is seriously flawed